2015
DOI: 10.1177/0091026015607117
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Organizational and Supervisor Identification for Interactional Justice

Abstract: Interactional justice is an important management issue for government agencies because it arises from daily interpersonal interactions and thus affects subsequent working outcomes of civil servants. This study is aimed to investigate the differential mediating effects of organizational identification and supervisor identification to explain why interactional justice affects both organization-focused and supervisorfocused outcomes. Specifically, we predicted that organizational identification would mediate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
(152 reference statements)
1
10
0
Order By: Relevance
“…We found the positive ties between interpersonal cognitive identification of the group members that are not included into any subgroup, and their contribution into the group activities. This finding is consonant with other researchers that draw positive correlations between identification with colleagues and helping behavior (Farmer et al, 2015), and between identification with the supervisor and helping behavior (Carnevale et al, 2019), OCB-I (C. Zhao et al, 2016), and OCB-O and OCB-I (Wang & Jiang, 2015). Despite the fact that in our research the relationship was found only in a certain kind of group members who are not included into a subgroup, and using another OCB dimension, the consistency of the findings demonstrates a strong tendency for the relationship between the interpersonal identification and behavior.…”
Section: Discussionsupporting
confidence: 91%
“…We found the positive ties between interpersonal cognitive identification of the group members that are not included into any subgroup, and their contribution into the group activities. This finding is consonant with other researchers that draw positive correlations between identification with colleagues and helping behavior (Farmer et al, 2015), and between identification with the supervisor and helping behavior (Carnevale et al, 2019), OCB-I (C. Zhao et al, 2016), and OCB-O and OCB-I (Wang & Jiang, 2015). Despite the fact that in our research the relationship was found only in a certain kind of group members who are not included into a subgroup, and using another OCB dimension, the consistency of the findings demonstrates a strong tendency for the relationship between the interpersonal identification and behavior.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that OJP has both a direct and indirect effect on OCB, in other words, the fact that when OJP is analyzed with OI, the effect of OJP continues but decreases, means that OI (Ça glayan, 2014;Roohi, 2018;Mehdipour et al, 2019) are congruent with the results of the studies performed in different sectors showing that OI has an intervening variable role in the relationship (Cho and Treadway, 2010;Guangling, 2011;Choi et al, 2013;Demir, 2015;Wang and Jiang, 2015). The main reason why OJP has a positive effect on OCB among shipyard employees is the fact that people react based on their perceptions while constantly interacting their environments.…”
Section: Discussionmentioning
confidence: 67%
“…Another research with 130 employees working in headquarters of a multinational bank in Korea and 135 students (73 of them are MBA holders whilst 62 are undergraduate students) studying and working in USA, concluded that there is a significant relation between OJP and OI and argued that procedural justice has a direct impact on OCB and that OI plays a mediating role between procedural justice perception and OCB (Cho and Treadway, 2010). Further, another study with 202 local officials in the Sichuan province of China, determined that procedural and transactional justice impact the OIs of employees, that OIs positively affect their OCB and that OI plays a role of mediator in the relationship between procedural and transactional justice and OCB (Wang and Jiang, 2015). The findings of another study with 220 employees in a private organization in China, reported that OJP affects the OIs of employees, their OI levels positively affect their OCBs and that OI plays a role of mediator on the relationship between OJ and OCBs (Guangling, 2011).…”
Section: The Mediating Role Of Organizational Identificationmentioning
confidence: 99%
“…The perceived justice in the organization is the factor that creates trust in supervisor and organization onward. Many researchers have found that organizational justice has a positive relationship with organizational citizenship behavior at a statistical significant level (Cho & Dansereau, 2010;Saraih et al, 2015;Wang & Jiang, 2015;Zeinabadi & Salehi, 2011 …”
Section: Justicementioning
confidence: 99%